2021
DOI: 10.3390/jcm10215210
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Magnetic Stimulation in the Treatment of Urinary Incontinence: A Systematic Review and Results of Our Study

Abstract: Urinary incontinence (UI) is becoming an increasingly common health problem. UI treatment can be conservative or surgical. This paper focuses on the effectiveness of magnetic stimulation (MS) in the treatment of UI. We performed a systematic review in order to combine and compare results with results from our clinical study. A clinical prospective non-randomized study was carried out at the Ljubljana University Medical Center’s Gynecology Division. It included 82 randomly selected female patients, irrespective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 38 publications
0
24
0
2
Order By: Relevance
“…[22][23][24][25][26][27] MS uses similar TMS devices to target the peripheral nervous system (PNS) or peripheral magnetic stimulation (PMS) for investigational nerve conduction studies, [28][29][30][31] to treat different neurological [32][33][34] and musculoskeletal impairments. [34][35][36][37][38][39][40][41] In a typical PMS session, a standard figure-of -eight or a circular coil is applied over specific muscles or nerves, such as the trapezius and the deltoid, to treat migraine, 34,42,43 or the sacral nerve to treat urinary and fecal incontinence. [44][45][46] Furthermore, PMS is increasingly being studied for stimulating both the spinal root and the peripheral nerve levels in treating neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] MS uses similar TMS devices to target the peripheral nervous system (PNS) or peripheral magnetic stimulation (PMS) for investigational nerve conduction studies, [28][29][30][31] to treat different neurological [32][33][34] and musculoskeletal impairments. [34][35][36][37][38][39][40][41] In a typical PMS session, a standard figure-of -eight or a circular coil is applied over specific muscles or nerves, such as the trapezius and the deltoid, to treat migraine, 34,42,43 or the sacral nerve to treat urinary and fecal incontinence. [44][45][46] Furthermore, PMS is increasingly being studied for stimulating both the spinal root and the peripheral nerve levels in treating neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Although the US FDA has approved extracorporeal FMS for UI treatment since 1998, few studies in the literature have assessed the efficacy of safety for this procedure. Lukanovi’c et al [ 8 ], in a recent systematic review on the effectiveness of magnetic stimulation in the treatment of UI, which included articles published between 2010 and 2020, showed that only 12 studies were eligible. These studies, which have mainly considered patients with SUI, used different devices with various magnetic field power (up to a maximum of 2.5 Tesla), different diagnostic methods to define the type and severity of UI and different tools to evaluate outcomes (standardized questionnaires are sometimes used).…”
Section: Discussionmentioning
confidence: 99%
“…It is based on Faraday’s law of magnetic induction, whereby a time-varying magnetic field induces electrical activity that depolarizes the nerves and causes the pelvic floor muscles to contract or relax. Repeated activation of the terminal motor nerve fibres and the motor end plates tend to build muscle strength and endurance [ 8 , 10 ]. The main stimulation targets are the afferent branches of the pudendal nerve to inhibit the detrusor muscle through central reflexes and the efferent nerve branches to facilitate strengthening of the pelvic floor muscles and increase the tonus of the urethral sphincters, thereby inhibiting the detrusor muscle through the guarding reflex [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations